1974
DOI: 10.1144/gsl.qjeg.1974.007.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Review of groundwater pollution from waste disposal sites in England and Wales, with provisional guidelines for future site selection

Abstract: Summary Preliminary results are presented of a multi-authority review of the water pollution hazard represented by 2494 landfill sites in England and Wales. Of these, desk studies indicate that only 51 represent a serious pollution risk to major or minor aquifers. River authorities have classified 80 sites as being unacceptable for future use out of 714 locations they have examined. In defining provisional guidelines for the selection of landfill sites, a generalized threefold classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 1 publication
1
3
0
2
Order By: Relevance
“…Turajo et al [ 23 ] explored the issues of burial practice and its effect on groundwater pollution in Maiduguri, Nigeria and reported that the groundwater samples from boreholes at very close proximity to the cemetery were characterised by high pH values among other physicochemical properties and had significantly higher concentrations compared with the values obtained from boreholes located far distance away from Cemeteries. Turajo et al [ 23 ] findings were in support of earlier study by Gray et al [ 24 ] in England that reported a reduction in contamination levels as the distance from cemeteries increases. In Benin City, Idehen [ 25 ] conducted univariate and multivariate analyses on the dataset obtained from characterization of groundwater samples from cemetery vicinity and identified Cl, NO₃, SO₄, BOD₅, Na, K, Mg, Pb, Mn, Cu, Ni, and Zn as parameters that could bear imprints of burial leakage from cemeteries.…”
Section: Introductionsupporting
confidence: 76%
“…Turajo et al [ 23 ] explored the issues of burial practice and its effect on groundwater pollution in Maiduguri, Nigeria and reported that the groundwater samples from boreholes at very close proximity to the cemetery were characterised by high pH values among other physicochemical properties and had significantly higher concentrations compared with the values obtained from boreholes located far distance away from Cemeteries. Turajo et al [ 23 ] findings were in support of earlier study by Gray et al [ 24 ] in England that reported a reduction in contamination levels as the distance from cemeteries increases. In Benin City, Idehen [ 25 ] conducted univariate and multivariate analyses on the dataset obtained from characterization of groundwater samples from cemetery vicinity and identified Cl, NO₃, SO₄, BOD₅, Na, K, Mg, Pb, Mn, Cu, Ni, and Zn as parameters that could bear imprints of burial leakage from cemeteries.…”
Section: Introductionsupporting
confidence: 76%
“…Les rejets d'eaux usées sur les terrasses situées au nord du bassin et les lixiviats de l'ancienne décharge publique au niveau de l'oued Boukhara, un des affluents les plus importants de l'oued Nil, sont d'autres sources probables de cette contamination. Des études (GRAY et al, 1974;RUGGE et al, 1995) ont montré les dangers liés à la présence des décharges publiques à proximité des sources d'eau. De façon globale, l'évaluation des concentrations des métaux présents à l'état de trace dans l'eau reste une opération délicate et se heurte en permanence à des risques de contamination.…”
Section: Variations De L'activité De La Superoxyde Dismutase (Sod)unclassified
“…1.3. 104 The Founex Report, supra, note 99; Mostafa K. Tolba, "Only One Earth", Science for Better Environment, Proceedings of the International Congress on the Human Environment (Oxford, England: Pergamon Press Ltd., Kyoto,1975) 7, at pg. 14.…”
Section: Silent Springmentioning
confidence: 99%